Humanitarian organizations in the light of the Holy Quran and Sunnah - Ananzeh, Hassan Ali Hassan; Ananzeh, Feras Ali Alhamad (Journal of Islamic Sciences, 2019)
This study aims to shed light on the humanitarian organizations in light of the growing role of civil society organizations, including constructive and destructive, in addition to dealing with its emergence and development and the role that can play on the local and international arenas in the light of the guidance of the Koran and the Sunnah. The researcher has followed the inductive fundamentalist approach through the use of verses from the Koran supported by the interpretation of the interpreters and try to drop these interpretations on the lived reality through reference to the evidence from the Koran explicit, as well as the researcher inferred the Prophet’s Sunnah, coupled with the explanations of the hadith Hadith as well as his biography In the publication of the Islamic call, the researcher reached many results, the most important of which are the different philosophers of Greece and the Greeks in their contemplation of human organizations through their freshness to society and the extent of enrichment provided by Arab and Muslim philosophers in the conceptualization. The researcher reached the legitimacy of constructive humanitarian organizations such as advocacy, liberation and humanitarian relief and awareness- raising organizations and the fight against organizations with destructive orientations that target the nation and its unity as Zionist and atheistic organizations. In contrast, the study recommended that all constructive humanitarian organizations should be encouraged. The study recommended that the role of civil society organizations should be activated in parallel with government institutions so that they are of no help to them, as explained in the conclusion of the search.